PENGARUH FASILITAS, KUALITAS PELAYANAN DAN KOLEKSI BUKU TERHADAP MINAT BACA SISWA DI PERPUSTAKAAN SMK SWADAYA TEMANGGUNG - Desya Risti Riyani; Rahmaningtyas, Wisudani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Low reading interest among students in the school environment is a problem that needs to be addressed, considering that reading is the main foundation for improving learning quality and academic achievement. This study aims to determine the effect of facilities, service quality,and book collections on reading interest among students at SMK Swadaya Temanggung. This study uses a quantitative approach, with a research population of 1,741 students. The Simple Random Sampling method using the Slovin formula, resulting in 127 students as respondents. Data collection was conducted using a Likert scale questionnaire that had undergone validity and reliability testing. The collected data were analyzed using multiple linear regression testing with the help of SPSS 27, including Classical Assumption Testing, t-Test, F-Test, and Coefficient of Determination. The results of the study show that facilities and book collections have a positive and significant effect on reading interest, while service quality does not show a significant effect partially. Simultaneously, the three variables have a significant effect on reading interest with (R2) of 0.448.